2019
DOI: 10.5430/rwe.v10n2p38
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factor, Education & Training and PPE Impact on Safety Performance: A Study Among Construction Workers at SESCO Sub-station, Balingian, Sarawak

Abstract: Safety and health at workplace is an emergent concern in almost all parts of the world including developing countries such as Malaysia. Construction industry is one of the most hazardous industries with regard to work-related injury and fatality rates. Impact on the company would include loss working hours of injured employee, cost of repair and replacement of property and damages as well as increment in insurance premium. The purpose of the study is intended to examine the relationship between factors with sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Maharja, Faradisha & Panggeleng et al ( 2022) in their study found that the availability of PPE in the workplace has proven to be significant to the safety behavior of employees in the workplace. Kasuma, Ismailly, Ghaffari, Rusuli, and Gapor (2019) found that PPE is the most important factor affecting the safety performance of workers in the workplace. The availability of PPE is vital because it exists as a preventive measure against workplace hazards.…”
Section: Readiness Of Personal Protective Equipment (Ppe)mentioning
confidence: 99%
“…Maharja, Faradisha & Panggeleng et al ( 2022) in their study found that the availability of PPE in the workplace has proven to be significant to the safety behavior of employees in the workplace. Kasuma, Ismailly, Ghaffari, Rusuli, and Gapor (2019) found that PPE is the most important factor affecting the safety performance of workers in the workplace. The availability of PPE is vital because it exists as a preventive measure against workplace hazards.…”
Section: Readiness Of Personal Protective Equipment (Ppe)mentioning
confidence: 99%
“…The construction industry plays a crucial role in the national economy in developing countries such as Vietnam (Anaman & Egyir, 2019;Kasuma et al, 2019;Likhitruangsilp & Ioannou, 2004;Quyen, Phong, & Vy, 2017;Nguyen et al, 2016). According to Business Monitor International's forecast, the civil and industrial construction industry in Vietnam has been estimated to grow at an average rate of 6.6% per year from 2017 to 2025 (Ha & Lam, 2017;Ha & Nguyen, 2014;Ha & Tam, 2015;H.…”
Section: Introductionmentioning
confidence: 99%